Indian consensus on durability of glycemic control in type 2 diabetes management and role of oral antidiabetic drugs - Chawla, Manoj; Kalra, Pramila; Khanna, A. K.; Mahapatro, Sisir Kumar (International Journal of Research in Medical Sciences, 2021)
The prevalence of type 2 diabetes mellitus (T2DM) is increasing in an alarming way in India as well as across the globe. In order to minimize complications, there is a need to maintain good glycemic control in patients with T2DM and long-term durable glycemic control remains a challenge. Clinically, this challenge was addressed by step-wise intensification of therapy with additional antidiabetic drugs to maintain glycemic control. Various disease and patient-related factors as well as different antidiabetic agents influenced the durability of glycemic control differently. While understanding of the factors that influenced therapeutic outcomes had evolved, there was paucity of information about the durability of glycemic control and the role of oral antidiabetic drugs (OADs) in achieving it. With an objective to understand the role of durability of glycemic response in the management of Indian patients with T2DM, 4 advisory board meetings attended by 48 physicians from across the country were conducted in Mumbai, Delhi, Kolkata and Bengaluru. There was consensus to consider durability of glycemic control as an important goal in the management of T2DM. Personalized approach in T2DM management along with early initiation of dual combination therapy were recommended to achieve durability. Age group of patients, body mass index, glycated hemoglobin levels at diagnosis, presence or absence of comorbidities and complications are important factors that need to be considered before initiating dual combination therapy for patients with T2DM.